Solitaire Flow-Restoration Device for Treatment of Acute Ischemic Stroke: Safety and Recanalization Efficacy Study in a Swine Vessel Occlusion Model - Jahan, R. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: The extended time window and theoretic reduction in hemorrhage make mechanical strategies an attractive approach in the treatment of patients with ischemic stroke. My purpose was to evaluate the recanalization efficacy and safety of the Solitaire FR Revascularization Device in a swine vessel occlusion model. MATERIALS AND METHODS: For recanalization efficacy, radio-opaque clots were used in 6 ascending pharyngeal arteries of the swine. Safety was assessed in 8 renal arteries with 3 passes of the device. Four vessels were harvested at 30 days, and 4, at 90 days, with microscopic examination to assess vessel damage. RESULTS: On deployment, immediate flow was seen in 3/6 vessels; and on retrieval, TIMI-3 recanalization was seen in 6/6. Vasospasm, which resolved on follow-up angiography with no distal emboli or vessel damage, was noted. In the renal vessels, safety evaluation findings were unremarkable, with the exception of 2 vessels harvested from a kidney at 90 days. These 2 vessels appeared without damage on microscopy; however, angiography showed shrinkage of the entire kidney, which was attributed to damage and stenosis of the main renal artery at the site of the guide-catheter insertion, likely leading to a chronic low-flow state and resultant atrophy of the entire kidney. CONCLUSIONS: The Solitaire Device showed good recanalization efficacy with acceptable safety. The unique stent-like design allows immediate flow restoration, a distinct advantage of the device. On the basis of this study, the device has good potential as a tool in the treatment of patients with ischemic stroke.